2010
DOI: 10.1093/jxb/erq108
|View full text |Cite
|
Sign up to set email alerts
|

Genotype effects on internal gas gradients in apple fruit

Abstract: A permeation-diffusion-reaction model was applied to study gas exchange of apple fruit (Kanzi, Jonagold, and Braeburn) as effected by morphology and respiratory metabolism. The gas exchange properties and respiration parameters of the fruit organ tissues were measured. The actual internal tissue geometry of the fruit was reconstructed from digital fruit images and the model was solved over this geometry using the finite element method. The model was validated based on measurements of internal gas concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 30 publications
3
77
3
Order By: Relevance
“…This would imply that both O 2 and CO 2 would be transported mostly through the intercellular space rather than through the cells and that the apparent diffusivity of CO 2 in tissue would also be smaller than that of O 2 . Yet, in previous research, we found the opposite (Ho et al, 2010). A possible explanation of this paradox would be that the larger solubility of CO 2 in water would mean that the cells would provide an additional transport route for CO 2 .…”
Section: Transport Routes For O 2 and Cocontrasting
confidence: 61%
See 4 more Smart Citations
“…This would imply that both O 2 and CO 2 would be transported mostly through the intercellular space rather than through the cells and that the apparent diffusivity of CO 2 in tissue would also be smaller than that of O 2 . Yet, in previous research, we found the opposite (Ho et al, 2010). A possible explanation of this paradox would be that the larger solubility of CO 2 in water would mean that the cells would provide an additional transport route for CO 2 .…”
Section: Transport Routes For O 2 and Cocontrasting
confidence: 61%
“…While microscale sensors are available for O 2 (Rolletschek et al, 2004;Ho et al, 2010), for various practical reasons it was not feasible to carry out local O 2 measurements at well-specified positions in the same samples that were used for 3-D synchrotron imaging. Also, such invasive measurements would most likely have an effect on the local gas transport itself.…”
Section: Comparison Of Computed Microscale Gas Exchanges With Measurementioning
confidence: 99%
See 3 more Smart Citations